A reversible cell penetrating peptide-cargo linkage allows dissection of cell penetrating peptide- and cargo-dependent effects on internalization and identifies new functionalities of putative endolytic peptides - Morris, Daniel P.; Snipes, Lucy C.; Hill, Stephanie A.; Woods, Michael M.; Mbugua, Maria M.; Wade, Lydia R.; McMurry, Jonathan L. (Frontiers in Pharmacology, 2022)
Cell penetrating peptides (CPPs) are a promising technology for therapeutic delivery of macromolecular cargos. CPPs have generally used covalent linkages to cargo, ensuring a common fate as one molecule. Conversely, our CPP-adaptor, TAT-CaM, noncovalently binds calmodulin binding sequence (CBS)-containing cargos in calcium rich media then dissociates in the calcium-poor endosomal environment following internalization, enhancing endosomal escape relative to standard CPPs. In this study, we report cell entry of positively charged protein cargos that were not increased by TAT-CaM while cargos based on the negatively charged maltose binding protein (MBP) displayed little intrinsic internalization but were internalized by TAT-CaM. In addition, association of positively charged proteins with negatively charged nucleic acids reduced internalization. This evidence points to the dominant role cargo charge plays in apparent CPP effectiveness. There has been little systematic investigation as to how interaction between CPPs and cargos impacts internalization efficiency. Our adaptors provide a tool that allows combinatorial assays to detect emergent properties. Toward this end we added 4 endolytic peptide (EP) sequences between cargo CBS and MBP moieties to create 4 new cargos and between TAT and CaM to create 4 new adaptors. The new cargos were assayed for internalization alone and with a panel of CPP-adaptors to identify combinations that displayed increased internalization efficiency or other properties. Among the most important results, addition of the EP LAH4 improved adaptor performance and provided some CPP capability to cargos. MBP-LAH4-CBS was internalized more effectively by most adaptors, suggesting this sequence has general stimulatory ability. Two other EPs, Aurein 1.2 and HA2, also provided some CPP capability to their MBP cargos but were unexpectedly antagonistic to internalization by most adaptors due to retention of adaptor/cargo complexes on the cell surface. We thus identified LAH4 as stimulator of internalization in both adaptors and cargos and uncovered new functionality for Aurein 1.2 and HA2, which may be related to their identification as EPs. Future experiments will test new endolytic capabilities made possible with combinatorial approaches.